Improving students' understanding of basic programming concepts through visual programming language: The role of self-efficacy - Tsai, Chun-Yen (Computers in human behavior, 2019)
This study implemented an intervention using a visual programming language (VPL) to improve students' understanding of basic programming concepts. The VPL learning environment may reduce the difficulties in programming language learning and is suitable for teaching students who are not computer science majors. Meanwhile, the difference in learning performance of students with different levels of self-efficacy was explored. The basic programming concepts included sequence, condition, and loop. A quasi-experimental design was employed in this study. The participants consisted of 180 students taking general courses at a university in southern Taiwan. Instruments included the Test of Basic Programming Concept and a self-efficacy questionnaire. The results indicated that the VPL teaching improved learners' understanding of basic programming concepts in the experimental group. The effect on basic programming concepts was especially large in students with moderate and low self-efficacy. The implication is that the VPL has extensive potential for programming courses in the general education of universities. •This study implemented an intervention using the visual programming language.•App Inventor 2 was used to improve students' basic programming concepts.•The design-based learning strategy was used to the better understanding of the effects.•The visual programming language teaching improved learners' concepts.•The effect was especially large in students with moderate and low self-efficacy.